Cancer-related hypercalcemia in oral cancer. Issue 6 (June 2018) - Lin, T.-C.; Liang, K.-L.; Lee, L.-C.; Hsu, C.-Y.; Yen, T.-T.
Abstract: Cancer-related hypercalcemia (CRH) is a critical paraneoplastic disorder in advanced cancer patients. In clinical practice, patients with CRH have a poor prognosis. The medical records of 3198 oral cancer patients with CRH diagnosed at Taichung Veterans General Hospital from 1 January 2003 to 31 December 2015 were reviewed. The criteria for patient enrolment were a diagnosis of hypercalcemia or the use of antihypercalcemia medication. Patients who met any of the following criteria were excluded: use of total parenteral nutrition, incomplete serum calcium data, and unknown date of death. The total incidence of CRH was 6.95‰ per year. A total of 91 patients were enrolled; their median survival time was 28 days. The patients were divided into two groups by survival time, with a cut-off point of 30 days. Reduced serum albumin, leucocytosis, and clodronate use had a statistically significant effect on survival in the univariate analysis (all P < 0.05). Forty-five patients (49.5%) had recurrence of CRH, of whom nine died within 30 days. These nine patients had a shorter interval to the first episode of CRH recurrence (median 13 days) than those who survived ≥30 days (median 28 days) ( P < 0.001). It was observed that a short interval to the first episode of CRH recurrence is a poor prognostic factor.